Dynamic Relationship among Tax Evasion, Control over Corruption and Political Accountability: A Case Study of Pakistan - Razzaq, Asif; Nazir, Rabia; Adil, Fareeha (International Journal of Economics and Financial Issues, 2020)
Public provisions and public resources are crucial for achieving the economic development of any economy. The government needs revenue in order to provide these public provisions. Pakistan faces grave challenges to enhance its revenue targets. Tax evasion is one of the factors for this shortage of tax revenues in Pakistan. Therefore, the study employs a co-integration approach to establish short term and long-term relationships between tax evasion, governance (measured as control over corruption), and political accountability. Engle-Granger approach is used to measure ECM while Johansen cointegration test is conducted for long-run relationships among the variables. The study explores that both the control over corruption and the political accountability reduce tax evasion, while the lag value of tax evasion and tax evasion to GDP determines the behavior of taxpayers. Error correction term shows that there is 22% speed of adjustment in the short run to restate the equilibrium while there is a weak long-run relationship among these variables. Keywords: GDP, Tax evasion, corruption, political accountability, co-integration JEL Classifications: H2, H3, H8 DOI: https://doi.org/10.32479/ijefi.10211